The complete mitochondrial genome sequence and phylogenetic position of Xylota coquilletti (Soo-Hyun Jeong, Ho-Yeon Han 2019) (Diptera: Syrphidae: Eristalinae: Xylotini). Issue 8 (3rd August 2022) - Pan, Zelin; Ci, Xingfa; Zheng, Renwen; Tang, Qingfeng; Lu, Sihan
Abstract: The complete mitochondrial genome sequence of the Xylota coquilletti (Diptera: Syrphidae: Eristalinae: Xylotini) was sequenced and reported for the first time. The whole genome was 15, 920 bp in length with the 37 classical eukaryotic mitochondrial genes and a control region. The nucleotide composition was included by 40.5% A, 39.6% T, 11.7% C, and 8.2% G, meaning that A + T (80.1%) was much greater than C + G (19.9%). It consisted of 22 transfer RNA genes (tRNAs), two ribosomal RNA genes (rRNAs), 13 protein-coding genes (PCGs), and a control region (CR). Phylogenetic analyses were performed using 13 PCGs and it was found that Xylota coquilletti was sister to Ferdinadea cupera . All this information could complement the mitochondrial data for a new tribe of Eristalinae.